SEKOLAH KHUSUS OLAHRAGA DI KABUPATEN KUBU RAYA - Azzahra, Anandea Maharani; Irwin, Irwin; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
The Ministry of Youth and Sports has issued a National Sports Grand Design (DBON) policy as stated in Presidential Regulation (Perpres) Number 86 of 2021 to improve sports achievements in Indonesia. It targets Indonesia to rank in the top five at the Olympics and Paralympics in 2045. DBON policy is expected to help the direction of sports development in West Kalimantan, which is experiencing a decline in performance at the 2021 PON (National Sport Week) XX Papua event. In an attempt to improve sports performance in West Kalimantan, sports education can be a solution through Special Sports Schools (SKO) which develop potential athletes in West Kalimantan. Kubu Raya Regency has the potential to be developed into a location for the development of sports education supported by administrative conditions and geographical conditions of Kubu Raya Regency. The design of a Sports School in Kubu Raya Regency aims to provide facilities that can accommodate learning, teaching, and training activities for outstanding sports students in high school in the province of West Kalimantan. Sports learning is focused on 14 leading sports in Indonesia, according to DBON, and leading sports in West Kalimantan. The design of a Sports School in Kubu Raya Regency uses the glass box (rational) method, where data collection and analysis form the basis for developing ideas to harmonize students' physical and mental development in area function zones, provision of facilities, area design, and building designs within the Sports School area.